Results of traction followed by hip spica cast for closed fracture shaft of femur in children from 2 years upto 10 years of age: experience from a remote centre in North India - Muzzafar, Khalid; Bijyal, Arpan; Malik, Anzar Tariq; Ali, Nadeem; Ghani, Abdul (International Journal of Research in Medical Sciences, 2022)
Background: Fracture shaft of femur is a common fracture in children, with treatment from conservative in form of skin traction to intramedullary nailing depending on age. Conservative treatment is mostly used upto six years of age, while for children more than 12 years surgery is usually preferred. We extended conservative in form of hip spica cast till 10 years of age. This study evaluates results of skin traction followed by spica cast in children upto 10 years of age. Methods: Study was done in GMC Doda from April 2019 to March 2022. 47 patients were enrolled for study, patients were initially given skin traction to get alignment which was followed by spica cast. Patients were evaluated at 3, 6, 9 and 12 weeks, final follow up was done at 6 months. Results: Out of 47 children, 4 patients were lost to follow up. Average age of children was 5.83 years. Mode of trauma was mostly RTA or fall from height. Average duration of traction was 9.14 days and average stay in hospital was 11.5 days. Average union time was 8.36 weeks. We had significant limb length discrepancy or angulation in 6 (13.9%) of our patients. Conclusions: skin traction followed by spica cast gives good results in fracture shaft femur in children upto 10 years of age.